First-principles molecular dynamics simulations at solid-liquid interfaces with a continuum solvent - Sanchez, Veronica Muriel (2009)
Continuum solvent models have become a standard technique in the context of electronic structure calculations, yet no implementations have been reported capable to perform molecular dynamics at solid-liquid interfaces. We propose here such a continuum approach in a density functional theory framework using plane-wave basis sets and periodic boundary conditions. Our work stems from a recent model designed for Car-Parrinello simulations of quantum solutes in a dielectric medium [D. A. Scherlis, J. Chem. Phys. 124, 074103 (2006)], for which the permittivity of the solvent is defined as a function of the electronic density of the solute. This strategy turns out to be inadequate for systems extended in two dimensions: the dependence of the dielectric function on the electronic density introduces a new term in the Kohn-Sham potential, which becomes unphysically large at the interfacial region, seriously affecting the convergence of the self-consistent calculations. If the dielectric medium is properly redefined as a function of the atomic coordinates, a good convergence is obtained and the constant of motion is conserved during the molecular dynamics simulations. The Poisson problem is solved using a multigrid method, and in this way Car-Parrinello molecular dynamics simulations of solid-liquid interfaces can be performed at a very moderate computational cost. This scheme is employed to investigate the acid-base equilibrium at the TiO2 -water interface. The aqueous behavior of titania surfaces has stimulated a large amount of experimental research, but many open questions remain concerning the molecular mechanisms determining the chemistry of the interface. Here we make an attempt to answer some of them, putting to the test our continuum model.